Multimodal composing and L2 learning: Rationales, empirical evidence, and future research agendas - Manchón, Rosa M. (Studies in Second Language Learning and Teaching, 2026)
This paper extends the inquiry into the language learning affordances of multimodal composing through a critical examination of past theoretical and empirical developments in the domain. It starts with an overview of a controversy related to theoretical positions on the language learning potential of multimodal writing. This is followed by a research synthesis of the theoretical frameworks, aims, methods, and findings of the relevant empirical research. It is concluded that research insights robustly support the centrality of linguistic processing in individual and collaborative multimodal writing conditions, which, in turn, appears to be the result of an intricate interplay of writer-internal and task-related factors. On the basis of this analysis, substantive and methodological directions for future empirical initiatives are proposed, crucially including a greater focus on language learning gains, as opposed to the prevailing emphasis on effects on performance.